A Development of An Air Conditioning Cleaning Tray - MOHAMAD HISYAM, AHMAD SIRAAJ; ABDUL RAHMAN, MOHD FAHMI (Progress in Engineering Application and Technology, 2022)
This research purpose is to develop a product that will achieve the main objectives of this research which is firstly, to identify the risk faced by users of chemical cleaning solution. This objective is analysed with the help of the literature review and also data collection via Google Form questionnaires. On the basis of the results of the survey, the average respondents based on mean score were agreed (1.00 – 2.40) that they had use a chemical cleaning agent during the cleaning process of their air conditioning unit. They also know the meaning of the corrosive and poisonous symbol on the labelled bottle of the chemical cleaning agent. Secondly, to evaluate the cleaning time can be reduced efficiently. The questionnaires of this objectives is asked and the mean score and standard deviation, (M = 1.02, S.D = 0.158) was around (1.00-2.40), which meant the average of the respondents were agreed on the time and safety risk faced by users of chemical cleaning solution among air conditioning servicing users. Thirdly, is to propose a suitable product to improve the cleaning process and safety. This objective is asked in the questionnaires and the mean score and standard deviation mean, (M = 1.08, S.D = 0.267) was around 1.00-2.40, which meant the average of the respondents were agreed to the idea of a development of a product which can prevent damage or irritation due to the spill of chemical cleaning agent to the skin or surrounding and to save up the cleaning time of an air conditioning unit. This product is supported by data received through questionnaires distributed to vendors, servicing technician and public user to receive feedback on their knowledge on the risk of chemical cleaning agent, cleaning time reduction and also product development. Through the data received the objective are achieved. In conclusion, the vendors, servicing technicians and public users agreed on the development of the product to reduce the risk they face with the use the chemical cleaning agent and a product to reduce the time needed to clean an air conditioning unit with the use of a chemical cleaning agent or solution to the air conditioning unit.